A Silenus Mask and Other Cult Symbols on Hadrian’s Alexandrian Dichalkoi - Holman, Tyler (KOINON: The International Journal of Classical Numismatic Studies, 2021)
This paper will examine two poorly understood reverse types found on Hadrianic dichalkoi from Alexandria. It argues that the objects depicted on these reverses should be identified as a mask of Silenus and a torch. It further argues that these types should be interpreted within the wider context of Hadrian’s Alexandrian dichalkoi, which almost exclusively feature isolated depictions of cult objects and symbols.